Configuring green behaviors in hospitality: a drive-state-pressure model analysis of institutional and individual dynamics - Zhang, Jun; Cui, Junbo; Chai, Xinchen; Li, Siqi (Frontiers in Psychology, 2025)
IntroductionThe hotel industry creates significant economic value but also intensifies environmental challenges. Frontline employees’ green behaviors (EGB) are crucial for translating organizational sustainability commitments into practice. This study applies the Drive–State–Pressure (DSP) model to examine how institutional pressures and individual agency jointly shape EGB.MethodsSurvey data were collected from 356 hotel employees in China. Fuzzy-set Qualitative Comparative Analysis (fsQCA) was used to explore configurational pathways leading to task-oriented green behavior (TGB) and voluntary green behavior (VGB).ResultsCoercive, normative, and mimetic pressures promote TGB primarily through compliance, whereas VGB is driven by autonomy and normative alignment. Distinct combinations of pressures and individual states highlight the complex mechanisms underlying EGB.DiscussionThe findings extend institutional theory by bridging macro- and micro-level perspectives through the DSP model and offer practical strategies for sustainability governance. Methodologically, the study demonstrates the value of fsQCA for capturing configurational interactions in employee green behaviors.